2020
DOI: 10.3390/ma13153264
|View full text |Cite
|
Sign up to set email alerts
|

Biological Cell Investigation of Structured Nitinol Surfaces for the Functionalization of Implants

Abstract: Expandable implants including shape memory alloy (SMA) elements have great potential to minimize the risk of implant loosening and to increase the primary stability of bone anchoring. Surface structuring of such elements may further improve these properties and support osteointegration and bone healing. In this given study, SMA sheets were processed by deploying additive and removal manufacturing technologies for 3D-printed surgical implants. The additive technology was realized by applying a new laser beam me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Due to the functional properties of nitinol SMAs, their biomedical application has proven successful by increasing the possibility as well as the performance quality of minimally invasive surgeries. The nickel-titanium SMA is highly biocompatible, which makes it useful in orthopedic implants, surgical instruments, cardiovascular devices, and orthodontic devices [6,7]. Nitinol SMA is categorized into two different types, namely shape memory and superelastic.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the functional properties of nitinol SMAs, their biomedical application has proven successful by increasing the possibility as well as the performance quality of minimally invasive surgeries. The nickel-titanium SMA is highly biocompatible, which makes it useful in orthopedic implants, surgical instruments, cardiovascular devices, and orthodontic devices [6,7]. Nitinol SMA is categorized into two different types, namely shape memory and superelastic.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high proportion of titanium in Nitinol, a good connection could be achieved. Another of our studies has already shown that the structuring technology of the anchoring elements is suitable for implantology due to its good biocompatibility [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hybrid combination of biocompatible, medical standard materials (Ti6Al4V powder and NiTi SMA) using LPBF showed that it is mechanically suitable to manufacture anchoring elements made of Ti6Al4V on NiTi SMA. In addition, our own preliminary investigations proved that the resulting structure, made of NiTi and Ti6Al4V, is biocompatible [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the application of LPBF technology of NiTi-SMA with TTi6Al4V offers a great potential to functionalize standard titanium bone implants. Our preliminary investigations have already demonstrated the biocompatibility of the compound [ 18 ].…”
Section: Introductionmentioning
confidence: 99%